"Twisted Desires, " Boy-Lovers, and Male–Male Cross-Generational Sex in the Late Ottoman Empire (1912–1918). Issue 1 (1st March 2020) - Kayaal, Tuğçe
Abstract: This article explores the condemnation of male–male cross-generational sexual practices in the Ottoman Empire during World War I (1914–1918) through a sexual harassment case that took place in an orphanage in Konya. Relying on the police registers and incorporating individual testimonies of orphan boys who were sexually abused by the headmaster, Münir Bey, I explore the wartime political and sexological discourses on cross-generational homoerotic sexual practices against the backdrop of the institutionalization of heterosexual sex. I argue that, rather than the act of sexual abuse itself, in the wartime ideological climate it was the sexual interaction between same-sex individuals that alarmed Ottoman state and society and forced them to take action against it. Male–male cross-generational sex and homoeroticism itself became bigger crimes than the act of sexually abusing underage individuals.